Rhetoricity at the End of History: Defining Rhetorical Debility under Neoliberal Colonialism. Issue 1 (1st January 2022) - Hashlamon, Yanar
ABSTRACT: This essay conceptualizes and applies a theory of rhetorical debility to new materialist rhetorical studies. Drawing from critical disability studies, rhetorical debility frames the ways that hierarchical human and nonhuman relations can inhibit certain rhetoricities while enabling others under neoliberalism. This theory extends the concept of "rhetorical capacities, " located within a genealogy of new materialist and posthuman thought in rhetorical studies, in response to intersectional critique of new materialism from Indigenous scholars and disability studies. The essay demonstrates rhetorical debility's applicability to transnational sites of oppression along axes of disability, colonialism, and neoliberalism through a case study analysis of Palestinian protest rhetoric.